Farm safety—Time to act. (31st May 2018) - Lower, Tony; Temperley, John
Abstract: Issues addressed: Agriculture is recognised as a highly dangerous sector worldwide; hence, the use of evidence‐based solutions to address injury‐related incidents is critical to prevention. The main of this article was to determine the potential for prevention by use of existing controls based on deaths data from 2001‐2016. Methods: This study assesses data from the National Coroner's Information System for the period 2001‐2016 in regard to unintentional farm injury deaths in Australia (n = 1271). The six leading causes of death (tractors, quads [ATVs], water/dams, farm utilities [pickups], motorcycles and horses: n = 644) are reviewed against existing evidence‐based practice recommendations to ascertain the potential capacity to prevent and/or ameliorate the severity of the fatal incidents. Projections of economic costs associated with these incidents in the past five years (2012‐2016) are outlined. Results: Of the cases involving the six leading agents (n = 644), 36% (n = 235) have the potential to be prevented with the use of designated evidence‐based controls. Meanwhile, the costs attributed to deaths involving the six leading agents in the 2012‐2016 period, exceeded $313 million. Conclusions: Farm injury incidents and their related economic costs can be reduced by enhanced adoption of the existing evidence‐based controls. So what: Farm safety efforts in Australia require reinvigoration and funding to focus on evidence‐based controls supported by enforcement to attain maximum impact.